Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3961/jpmph.21.385
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal Distribution of Suicide Risk in Iran: A Bayesian Hierarchical Analysis of Repeated Cross-sectional Data

Abstract: Objectives: We aimed to estimate the space-time distribution of the risk of suicide mortality in Iran from 2006 to 2016.Methods: In this repeated cross-sectional study, the age-standardized risk of suicide mortality from 2006 to 2016 was determined. To estimate the cumulative and temporal risk, the Besag, York, and Mollié and Bernardinelli models were used.Results: The relative risk of suicide mortality was greater than 1 in 43.0% of Iran’s provinces (posterior probability >0.8; range, 0.46 to 3.93). The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…My suggestion would be in line with the authors’ to incorporate socio-economic and cultural risk factors in spatiotemporal analysis for suicide. Other similar international studies such as in USA, 9 Brazil, 10 and Iran 11 successfully demonstrated the association of high-risk areas with other risk factors such as opioid use, marital status, race, and gender. Authors of the current study could center their effort in examining the risk factors in new and persistent hotspots of suicide, and thereby adjoin relevant specific suggestions to the policy makers to assist in attenuating the suicidal risk globally, in conjunction with the spatiotemporal patterns of suicide.…”
mentioning
confidence: 73%
“…My suggestion would be in line with the authors’ to incorporate socio-economic and cultural risk factors in spatiotemporal analysis for suicide. Other similar international studies such as in USA, 9 Brazil, 10 and Iran 11 successfully demonstrated the association of high-risk areas with other risk factors such as opioid use, marital status, race, and gender. Authors of the current study could center their effort in examining the risk factors in new and persistent hotspots of suicide, and thereby adjoin relevant specific suggestions to the policy makers to assist in attenuating the suicidal risk globally, in conjunction with the spatiotemporal patterns of suicide.…”
mentioning
confidence: 73%